Integrating state-owned enterprises (SOEs), agro-economics, and sustainability: A systematic literature review on contract farming mechanism - Akbar, Syahrir; Pradana, M. Nanda Rakha; Rahma, Aulia; Rahmah, Nindya Fadhila (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Contract farming has emerged as a strategic mechanism to bridge market access, reduce production risks, and empower smallholder farmers in agricultural economies. However, its effectiveness varies across institutional contexts, particularly in developing countries facing market failures and power imbalances. This study aims to systematically examine the integration of state-owned enterprises (SOEs) within contract farming mechanisms to enhance agro-economic performance and sustainability. Previous studies have primarily focused on private-led contract farming models, with limited exploration of public or hybrid institutional roles, especially those owned by local governments. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, this study analyzes 19 peer-reviewed articles published between 2020 and 2025. Thematic synthesis is applied to identify key patterns related to institutional involvement, economic impact, and sustainability dimensions. Findings: The findings reveal that the integration of (SOEs) into contract farming can improve farmers’ access to production inputs, ensure price stability, and support inclusive participation in the value chain, particularly when supported by clear regulatory frameworks and participatory governance. Moreover, models involving public institutions tend to align more closely with long-term sustainability goals such as environmental preservation and rural social equity. Conclusion: This study concludes that BUMD holds untapped potential in reshaping the governance of contract farming systems toward more equitable and sustainable outcomes. Novelty/Originality of this article: The novelty of this article lies in highlighting the strategic role of local public enterprises such as BUMD in agricultural contracting, an area that remains underexplored in existing literature.